Cholecystectomy Via Laparoscopy for Acute Cholecystitis - Fazli Subhan, Hafiz Gul Nasib Khan, Atif Iqbal, Shabir Ahmad, Sanaullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the outcomes of laparoscopic cholecystectomy among patients of acute cholecystitis. Study Design: Retrospective study Place and Duration: Jinnah International Hospital, Abbottabad and DHQ Hospital Battagram From Aug, 2021 to Jan, 2022. Methods: There were 170 cases of both genders were presented in this study. Included patients were aged between 12-70 years. Included patients had acute cholecystitis were underwent for cholecystectomy and standard open procedure. After obtaining written consent, participants' personal information was collected, including their age, sex, BMI, and geographic location. Patients were equally divided into two groups. 85 patients received LC in group I and 85 patients received open procedure in group II. Post-operative outcomes among both groups were compared in terms of complications, efficacy, surgery time and pain score. SPSS 23.0 was used to analyze all data. Results: Among 170 included patients, majority of the patients were females 105 (61.8%) and males were 65 (38.2%). Mean age of the patients was 37.07±16.67 years. Majority of the patients 125 (73.5%) had body mass index <25kg/m2 and 45 (26.5%) had BMI >25kg/m2. 70 (41.2%) were from urban areas and 100 (58.8%) patients were from rural areas. Frequency of gallbladder empyema was found in 110 (64.7%) cases followed by GB phlegmon in 48 (28.2%) cases and perforation in 12 (7.1%) cases. Mean operative time in group I was significantly lower 32.12±9.81 minutes and compared to group II 51.11±11.74 minutes with p value <0.02. Successful rate of LC was 85 (100%) and none of patient had bile duct injury. Post treatment, significantly fast recovery was found in LC group as compared to open surgery with p value 0.008. Frequency of complications was higher in group II 26 (30.6%) and as compared to group I 2 (2.4%). Lower pain score was found in LC group. Conclusion: We concluded in this study that the acute cholecystitis was successfully treated by laparoscopic cholecystectomy with faster relief and lower operative time as compared to open surgery. Except this low pain score and complication rate was minimum observed after surgery in patients underwent for LC. Keywords: Acute Cholecystitis, Laparoscopy, Open surgery, Complications, Pain score